Transformational Leadership Unleashed: Elevating Faculty Satisfaction through Psychological Capital - WANG, Xiuzhuo; PHAWITPIRIYAKLITI, Chaithanaskorn; PATTANAYANON, Pirayut; TERASON, Sid (Journal of Ecohumanism, 2024)
This study investigates the influence of transformational leadership on job satisfaction, with a specific focus on the mediating role of psychological capital in private universities in Guangxi. The main hypotheses are that transformational leadership directly affects job satisfaction and that psychological capital partially mediates this relationship. Participants included 460 teachers from 12 private universities in Guangxi, China, selected by multi-stage sampling. The research design is quantitative, employing structured questionnaires. Instruments used include validated scales for transformational leadership, psychological capital, and job satisfaction, all measured on a 5-point Likert scale. The findings reveal that transformational leadership significantly predicts job satisfaction, and psychological capital also significantly predicts job satisfaction while mediating the relationship between transformational leadership and job satisfaction. These results align with earlier research, confirming the positive impact of transformational leadership and psychological capital on job satisfaction. The study concludes that university administrators should develop transformational leadership skills and foster psychological capital among teachers to enhance job satisfaction and teaching quality. This offers practical guidance for the management and reform of private colleges and universities in Guangxi, with implications for future research to explore additional mediators or moderators and employ longitudinal designs to further understand these relationships.